Protocells: Subcompartmentalization and Pseudo‐Division of Model Protocells (Small 2/2021). Issue 2 (14th January 2021) - Spustova, Karolina; Köksal, Elif Senem; Ainla, Alar; Gözen, Irep
Abstract : In article number 2005320, Irep Gözen and co‐workers demonstrate that the spontaneous subcompartmentalization of model protocells is governed by the physicochemical interaction of the protocell membranes with mineral‐like solid interfaces. In the described experiments, several tens of compartments emerge on the basal membrane of each adhered model protocell. They are able to encapsulate small molecules from the external environment and maintain them within. The compartments become isolated daughter protocells when the enveloping membrane ruptures, which can be perceived as a form of primitive division.